Value creation and value capture from patents: Theory and implications for patent strategies - Xiaoyang Zhao; Yuanjing Guo; Jie Mi (Journal of Innovation & Knowledge (JIK), 2023)
This study uses biform game models to examine firms' patent deployment strategies that involve a choice between appropriating a patented technology to gain a unique competitive advantage or licensing the technology to a competitor in the product market. It addresses the question of under what circumstances firms use a patent appropriation strategy over a licensing strategy, or vice versa. By incorporating competitive and cooperative settings, this study develops theory and propositions to illustrate the mechanisms by which patent deployment strategies are chosen by an innovator or follower in a product market as a function of the characteristics of innovation, transaction costs, bargaining power, strategic interactions, and other market conditions. This study contributes to the literature by distinguishing between patent appropriability and value appropriation in a transactional network under rivalry. The model and its extensions provide new insights into appropriation strategies for patent portfolios, which are important intellectual assets in a knowledge-based economy.
Keywords: O30; O32; C70; 650; Appropriability strategy; Biform model; Patent deployment strategies